Leadership Style, Instructional Supervision Strategies, and Job Performance of College Instructors in the Local Colleges in Cavite - Alcances, Maria Lyn S.; Yango, Antonio R.; Bermudo, Pedrito Jose V. (Technium Social Sciences Journal, 2023)
The condition of school and the role of leadership are widely listed as must mediation for adopting the advancement, modernization, changes, and innovations in capacity building and teaching and learning practices (Lunenburg & Ornstein, 2021). This study aimed to determine the department heads’ leadership style and instructional supervision strategies as predictor of instructors’ job performance in the local colleges in Cavite. Specifically, it probed the relationship between the leadership style and instructional supervision strategies of department heads; leadership style and instructors’ level of job performance; and instructional supervision strategies and instructors’ level of job performance. Likewise, it probed the predictive ability of department heads’ leadership style and instructional supervision strategies, taken singly or in combination, of instructors’ level of job performance in the local colleges in Cavite. The findings unveiled that leadership style did not significantly predict instructors’ level of job performance. However, one of the sub-variables on instructional supervision which is non- directive significantly predicted the instructors’ level of job performance. Hence, there was one model to present the causal relationship of instructors’ job performance and instructional supervision strategies. It was concluded in the study that the department heads of local colleges used different styles of leadership. They used different instructional supervision strategies for the improvement of the instructors on their teaching. The more that the department heads use the appropriate leadership style, the more they know what instructional supervision strategies they will practice. The more that department heads use the best style of leadership, the higher the level of job performance of the instructors. The more that department heads use the proper instructional supervision strategies, the higher the performance of the instructors